Cluster-like molybdenum phosphide anchored on reduced graphene oxide for efficient hydrogen evolution over a broad pH range. Issue 61 (6th July 2016) - Yan, Haijing; Jiao, Yanqing; Wu, Aiping; Tian, Chungui; Zhang, Xiaomeng; Wang, Lei; Ren, Zhiyu; Fu, Honggang
Abstract : Cluster-like MoP particles were anchored on rGO with high uniformity, and exhibit superior electrocatalytic activity towards the HER. Abstract : Cluster-like molybdenum phosphide particles were anchored on reduced graphene oxide (MoP/rGO) with high uniformity by using phosphomolybdic acid as a molybdenum precursor based on a robust assembly–immobilization method. Benefiting from the small size, and even distribution of the MoP particles, the MoP/rGO hybrid exhibits superior electrocatalytic activity towards the hydrogen evolution reaction both in acidic and alkaline media.